Primary Arthrodesis or Open Reduction and Internal Fixation for Lisfranc Injuries: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Lachlan Mactier BEng(Hons); Genevieve Cox BSc(Hons); Rajat Mittal MBBS, FRACS; Mayuran Suthersan MBBS, FRACS (Foot & Ankle Orthopaedics)
Background: Lisfranc injuries are often managed surgically with primary arthrodesis (PA) or open reduction and internal fixation (ORIF); however, neither approach has been shown to be superior. This systematic review and meta-analysis assessed randomized controlled trials (RCTs) to compare the functional and surgical outcomes of PA and ORIF in the treatment of Lisfranc injuries. Methods: This study was performed as per the PRISMA protocol. Database searches were conducted on Cochrane, Embase, and PubMed libraries. Five RCTs were identified for inclusion involving 241 patients, of which 121 underwent PA and 120 underwent ORIF. Results: Statistically significant differences in visual analog scale pain score at 2 years (mean difference 0.89, 95% CI 0.18-1.59), patient satisfaction (OR 10.04, 95% CI 1.78-56.76), and all-cause return to surgery (OR 27.31, 95% CI 12.72-58.63) were observed, all favoring PA. There were no statistically significant differences between PA and ORIF with regard to American Orthopaedic Foot & Ankle Society midfoot scores at 2 years, 36-Item Short Form Health Survey (SF-36) scores, and unplanned return to surgery. Conclusion: This study showed significant improvement in pain at 2 years, patient satisfaction, and all-cause return to surgery favoring PA in all instances. Given ORIF often necessitates a second operation for hardware removal, it is to be expected that all-cause return to surgery is higher in ORIF groups. Overall, these results do not have the power to confer an advantage to a particular approach because of significant heterogeneity. Further studies should focus on larger patient cohorts and longer follow-up, or analysis stratified by patient demographics and injury presentation. In the absence of clinically significant differences, cost-benefit analyses should be considered to answer the question of whether to “fix or fuse” for Lisfranc injuries.